Pengaruh Penyuluhan terhadap Kepadatan Aedes aegypti dalam Pencegahan Demam Berdarah - Zulaikhah, Siti Thomas; Yusuf, Iwang (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2018)
Background: Dengue infection is a public health problem and until now, the dengue eradication efforts have not been successfuly. In Indonesia, the incidence is still high and widely transmitted there fore the more intensive vector control is required. The purpose of this study was to verify that the counseling program about mosquitonest eradication effect the density of Aedes. Method: The research was quasi experiment using one group pre and post test design, interventions about counseling of mosquito to eradication. Samples were gathered from health center around Ngaliyan area which consisted of 6 districts. Each district was taken 100 houses by simple random sampling, so the total samples are 600 and each samples were testedor the presence of Aedes aegypti’s larvaes. Pretest was conducted on May 2013 and postest on August 2013 by conducting entomological survey to determine the density of Aedes aegypti’s larvae. Respondents are received 3 times counseling. Results: Data about Larva Free Index (ABJ), Container Index (CI), House Index (HI) and Breteau Index (BI) were tested for normality using Shapiro Wilk, and all were normally distributed (p>0.05), the data were analyzed using t-paired test. The result of Larva Free Index variable analysis obtained were p=0.011, CI p=0.000, HI p=0.035 and BI p=0.004. Conclusion: Counseling about mosquito eradication effected on Aedes aegypti’s larvae so it can prevent the outbreak of dengue fever.